Proceedings of the Ocean Drilling Program 1996
DOI: 10.2973/odp.proc.sr.151.139.1996
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic Arctic Gateway Paleoclimate Variability: Indications from Changes in Coarse-Fraction Composition

Abstract: Coarse-fraction sediment (>63 µm) studies for Leg 151 Sites 908 and 909 have enabled us to reconstruct the paleoclimate since the early Miocene (18.0 Ma) of the Fram Strait, in order to better understand this gateway between the North Atlantic and the Arctic Ocean. Study of the grain-size distribution patterns (subfractions 63-125 µm, 125-250 µm, 250-500 µm, 500-1000 µm, and >IOOO µm plus the coarse-component composition) suggests possible seasonal ice-rafting starting as early as 14.0 Ma. Also shown is a clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 3 publications
2
72
0
Order By: Relevance
“…Furthermore, the record of ice-rafted debris (IRD) at other high latitude sites close to Greenland (e.g. Schaeffer and Spiegler, 1986;Fronval and Jansen, 1996;Wolf-Welling et al, 1996;Helland and Holmes, 1997) suggests the establishment of small-scale glaciations on Greenland large enough to reach sea level at around this time. However, based on the stratigraphic occurrence at Site 907 it is difficult to assess the detailed paleoecological affinities of B. bergenensis sp.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the record of ice-rafted debris (IRD) at other high latitude sites close to Greenland (e.g. Schaeffer and Spiegler, 1986;Fronval and Jansen, 1996;Wolf-Welling et al, 1996;Helland and Holmes, 1997) suggests the establishment of small-scale glaciations on Greenland large enough to reach sea level at around this time. However, based on the stratigraphic occurrence at Site 907 it is difficult to assess the detailed paleoecological affinities of B. bergenensis sp.…”
Section: Resultsmentioning
confidence: 99%
“…Based on mineralogical data from ODP sites 908 and 909 in the Fram Strait (Fig. 1), Wolf-Welling et al (1996) suggested that the West Spitsbergen Current reached the Fram Strait episodically during Plio-Pleistocene (between 1.9 and 1.2 Ma). Thus, this influx of water masses along west Svalbard could have created environments for contourites to develop (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only few details of the exact extent of sea ice are known for this period. A local glaciation at Svalbard is thought to have yielded a general strengthening of NHG at $ 6.9 Ma (Winkler et al, 2002) and an enhanced sea-ice extent at the Greenland Sea between $ 7.5 and 6.2 Ma (Wolf-Welling et al, 1996). The enhanced sea-ice extent would easily have resulted in a shift of the NCW formation area south towards the Norwegian Sea (Fig.…”
Section: Unit Suiii (75-45 Ma)mentioning
confidence: 99%